Penyuluhan Peningkatan Literasi Keamanan Data Dan Etika Bermedia Sosial SMPN 09 PangkalPinang - Saputra, Dhito; Aldi; Dhuha, Akhmad; Sabil, Ibni; Endraswari, Putri Mentari (Universitas Hamzanwadi, 2025)
The rise of digital technology requires students to understand the importance of protecting personal data and practicing ethical behavior in online interactions. This study presents a community outreach activity conducted at SMP Negeri 9 Pangkalpinang aimed at improving students' digital literacy, particularly in data security and social media ethics. Using a qualitative approach, the program included material presentations, interactive discussions, and an evaluative quiz. The results revealed that all participants successfully answered the quiz questions, indicating a strong grasp of the topics presented. The interactive learning method, combined with incentives, effectively increased student participation and comprehension. This initiative demonstrates the importance of structured educational efforts in developing responsible digital habits and awareness among adolescents.